Negotiating Ethnic and Religious Identities: Indonesian Chinese Muslims in Sharīʿah Compliant Business - Lukis Alam; Achmad Maimun; Muh Iqbal; Royan Utsany; Meredian Alam (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2025)
This research is focused on how Indonesian Chinese Muslim entrepreneurs in Jakarta and Surabaya negotiated dual identity through sharīʿah compliant business practices. In addition, the integration of confucian ethical values with Islamic principles to form innovative and ethical business models that resonated in Indonesian Muslim-majority society, was explored. Drawing on empirical methods, including fieldwork and document analysis, the entrepreneurs did not perceive sharīʿah law and Chinese cultural traditions as mutually exclusive. Regarding this viewpoint, a hybrid identity responsible for enhancing social legitimacy, fostering inclusive entrepreneurship, and expanding participation in the ḥalāl economy, was adopted. Prominent figures showed how Islamic ethics harmonized with Chinese heritage, particularly in zakāh distribution, ḥalāl innovation, and community welfare. As a result, the analysis contributed to the discourse on legal pluralism, minority inclusion, and contextual application of Islamic economic principles. The originality lies in its empirical focus on an understudied group—Indonesian Chinese Muslims—and the illustration of how cultural-religious hybridity offered a viable and inclusive model for sharīʿah based entrepreneurship in contemporary Indonesia, with practical implications for business and society.